Rheology of starch dispersions at high temperatures. Issue 4 (28th February 2020) - Ahuja, Amit; Lee, Reginald; Latshaw, Alina; Foster, Peter
Abstract: In the food industry, many food products experience extreme processing conditions of high temperature and high shear stresses. The measurements of sample behavior for water‐based formulations above 100°C is extremely challenging due to changes in material composition from the boiling of volatile ingredients. We have developed a high‐sensitivity, pressurized starch pasting cell (up to 5 bar) which utilizes a design free of mechanical bearings and seals, resulting in an order‐of‐magnitude improvement in torque sensitivity (1 μ N.m in oscillatory and 10 μ N.m in shear flows) compared to traditional pressure cells. A pressurized atmosphere in the cell suppresses boiling of the volatile components, allowing the characterization of the structure–property relationships of the sample over a range of testing conditions (−5 to 150°C) which simulate industrial processing and storage conditions. This cell is employed to investigate the pasting properties of a commercial starch dispersed in water. In situ gelatinization of starch dispersions of varying starch particle weight fractions ( ϕ ) subjected to a high temperature (120°C) at elevated pressure and at a fixed shear rate is studied. A phase transition, from an initial flowable starch slurry to a paste, takes place during which the viscosity evolves by several orders of magnitude. Typical parameters associated with the viscosity evolution during gelatinization such as onset temperature, peak temperature, and peak viscosity are analyzed to probe the impact of high temperature on the gelation process and the rheological properties of the final starch paste. Furthermore, yield stresses of the final paste, measured at 120°C, are examined for varying ϕ through traditional rheological methods such as flow ramps, oscillatory shear, and stress growth, demonstrating the capabilities of this cell for studies of steady shear and nonlinear viscoelastic behavior of the starch pastes. The yield stress values are found to be in good agreement when comparing various testing methods. Yield stresses range from 0.25 to 6.5 Pa for ϕ between 0.05 and 0.15, with 0.05 being the minimum starch weight fraction for which there is any measurable yield stress. The yield stress and the paste viscosity both scale with starch particle weight fraction as ( ϕ  −  ϕ c ) m, where ϕ c = 0.04 as no yield stress is observed for ϕ  ≤ 0.04. The exponent, m, for yield stress is found to be in the range of 1.15–1.4 depending on the analytical method used and the definition of yield stress while for peak and breakdown viscosities it is noted to be 1.6 and 1.1, respectively. The Herschel‐Bulkley model is found to fit the flow curves well. The starch pastes are found to exhibit shear‐thinning and significant thixotropic behavior.